2023
DOI: 10.1172/jci.insight.163856
|View full text |Cite
|
Sign up to set email alerts
|

Individual transcriptomic response to strength training for patients with myotonic dystrophy type 1

Abstract: Myotonic dystrophy type 1 (DM1), the most common form of adult-onset muscular dystrophy, is caused by a CTG expansion resulting in significant transcriptomic dysregulation that leads to muscle weakness and wasting. While strength training is clinically beneficial in DM1, molecular effects had not been studied. To determine whether training rescued transcriptomic defects, RNA-Seq was performed on vastus lateralis samples from 9 male patients with DM1 before and after a 12-week strength-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 50 publications
0
0
0
Order By: Relevance
“…CDKN1A, TP63) 55 , are negatively correlated with muscle strength in DM1 51 . Notably, recent findings from DM1 patients' transcriptomic response to strength training showed that CDKN1A is one of the few genes that is correlated to clinical benefits (i.e., the individuals that experienced greater clinical benefits from strength training showed a stronger reduction in CDKN1A expression) 56 . RNAseq performed in other tissues such as the frontal cortex showed an enrichment in inflammatory genes compared to healthy individuals, suggesting that the pro-inflammatory signature is a common feature in different DM1 tissues 57 .…”
Section: Discussionmentioning
confidence: 99%
“…CDKN1A, TP63) 55 , are negatively correlated with muscle strength in DM1 51 . Notably, recent findings from DM1 patients' transcriptomic response to strength training showed that CDKN1A is one of the few genes that is correlated to clinical benefits (i.e., the individuals that experienced greater clinical benefits from strength training showed a stronger reduction in CDKN1A expression) 56 . RNAseq performed in other tissues such as the frontal cortex showed an enrichment in inflammatory genes compared to healthy individuals, suggesting that the pro-inflammatory signature is a common feature in different DM1 tissues 57 .…”
Section: Discussionmentioning
confidence: 99%